The effect of toxic workplace environment mediated by organizational culture, work environment, organizational support and employee well-being on employee engagement in the hospitality - Cherlyn Cherlyn; Antony Sentoso (Institute of Computer Science (IOCS), 2022)
This study to test and analyze can affect toxic workplace to employee engagement form hotels in Batam City. This study uses toxic workplace as independent variables. Organizational culture, work environment, organizational support and employee well-being be mediated while employee engagement be dependent variable. The types in this study are determining and causal from reasons or comparative causal. Research sampling method which only selected respondent who are hotel workers in Batam City. Data processed using SmartPLS 3.0 software. The result research shows that toxic workplace environment to few variable are didn’t have big impact to employee engagemenyt.